Pattern in early years mathematics curriculum: a 25-year review of the status, positioning and conception of pattern in England. Issue 1 (2nd January 2023) - Gripton, Catherine
ABSTRACT: Pattern is fundamental to mathematical learning yet pattern has been conspicuously low key within early mathematics curriculum guidance in England despite evidence that it predicts later attainment in mathematics overall. Whilst recent curriculum changes have seen pattern afforded enhanced status, this is within a conception of pattern that marks a significant shift away from the evidence base. Through analysis of 25 years of early mathematics curriculum in England, this article identifies a curriculum landscape where pattern has been afforded little attention and narrowly framed. It finds that positioning pattern as a minor topic in mathematics potentially limits children's access to "powerful knowledge", in a critical realist sense, and to learning which is fundamental to deep, connected mathematical understanding. Recognition of pattern as powerful knowledge would position it as an essential, broad, central tenet of early childhood mathematics education and as an entitlement at the heart of national curricula.